Lessons on Community-Based Fire Prevention and Peatland Restoration - Purnomo, H.; Puspitaloka, D. (Center for International Forestry Research, 2023)
Ideas, narratives and arguments on preventing natural disasters and restoring ecosystems focus on raising awareness and fostering participation from all parties. Conventional research helps in understanding socioecological systems and their interactions, but governments, communities and donors want research that makes a difference. There is an urgent need for tangible change. Research conducted with full participation and an action-oriented approach is the solution. Participatory Action Research (PAR) is designed to bring real change on the ground. PAR is transdisciplinary in nature; it integrates approaches from various disciplines and draws on both local and global wisdom. This book aims to provide an understanding of the concepts, philosophical foundations and steps involved in implementing PAR, and is complemented by examples of fire prevention and community-based peatland restoration efforts implemented in Riau Province, Indonesia. We hope it can serve as a valuable resource for researchers, private sector operators, communities, NGOs, governments and practitioners involved in natural disaster prevention and ecosystem restoration.